Potassium ion battery positive electrode material and preparation method thereof

By doping manganese or nickel elements into the cobalt-based oxide positive electrode material, the orderly structure of alkali metal ions between layers is solved, and the structural instability of cobalt-based oxide positive electrode material is achieved through the charging and discharging process, and structural stability is achieved and the improvement of potassium ion diffusion path.

CN119447282AActive Publication Date: 2025-02-14SICHUAN CHAOYIHONG TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411879009.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-02-14
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

The existing cobalt-based oxide positive electrode materials have unstable structure during charging and discharging, resulting in multiple phase transformations and layer spacing changes, affecting electrochemical performance.

Method used

By doping manganese or nickel elements into layered cobalt-based oxides, the original interlayer alkali metal ions order structure is broken, and the interlayer alkali metal ions vacancies disordered structure is formed, the diffusion path of potassium ions is increased, and multiple phases are suppressed. Change.

Benefits of technology

The positive electrode material of potassium ion battery that maintains structural stability in electrochemical behavior is realized, reducing structural changes, improving the stability of the material and the diffusion path of potassium ions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447282A_ABST
    Figure CN119447282A_ABST
Patent Text Reader

Abstract

The invention provides a potassium ion battery positive electrode material and a preparation method thereof, the molecular formula of the potassium ion battery positive electrode material is NaxCoyAzO2, x, y and z are atomic numbers, and A is a transition metal element; wherein 0.5 < = x < = 1, 0.6 < = y < = 0.9, and 0.1 < = z < = 0.4. The preparation method of the positive electrode material of the potassium ion battery comprises the following steps: (1) placing cobalt salt, manganese salt or nickel salt, sodium salt and a solvent in a ball milling tank for ball milling to obtain viscous powder; (2) drying the viscous powder to obtain mixed metal powder; and (3) sintering the material to obtain the positive electrode material. The potassium ion battery positive electrode material provided by the invention can inhibit multiple phase changes during charging and discharging, reduce structural changes and keep an electrochemical structure stable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of potassium ion batteries, and in particular to a positive electrode material for a potassium ion battery and a preparation method thereof. Background Art

[0002] Among various potassium ion battery cathode materials, layered metal oxides have attracted widespread attention due to their small molar mass and large interlayer spacing, which can provide two-dimensional alkali metal ion diffusion channels.

[0003] In the related art, layered cobalt-based oxides provide capacity changes through the insertion / deinsertion of alkali metal ions between layers during the charge and discharge process. However, the multiple phase changes of cobalt-based materials during the charge and discharge process will lead to unstable material structure, and the changes in interlayer spacing caused by the insertion and extraction of alkali metal ions will aggravate the structural changes.

[0004] Therefore, in view of the above shortcomings, there is an urgent need for a potassium ion battery positive electrode material that can maintain structural stability during electrochemical behavior. Summary of the invention

[0005] In view of this, the present invention proposes a potassium ion battery positive electrode material and a preparation method thereof, which can provide a potassium ion battery positive electrode material that maintains a stable structure during electrochemical behavior.

[0006] The technical solution of the present invention is achieved as follows: The present invention provides a positive electrode material for a potassium ion battery, wherein the molecular formula of the positive electrode material for a potassium ion battery is Na x Co y A z O2, x, y, z are all atomic numbers, A is a transition metal element;

[0007] Among them, 0.5≤x≤1, 0.6≤y≤0.9, 0.1≤z≤0.4;

[0008] The transition metal element is selected from Mn and / or Ni.

[0009] On the basis of the above technical solution, preferably, the molecular formula of the positive electrode material of the potassium ion battery includes Na 0.7 Co 0.75 Mn 0.25 O2、Na 0.7 Co 0.6 Mn 0.4 O2、Na 0.7 Co 0.75 Ni 0.25 O2、NaCo 0.75 Mn 0.25 O2、Na 0.5 Co 0.75 Mn 0.25 O2、Na0.7 Co 0.8 Mn 0.1 Ni 0.1 One of O2.

[0010] According to another aspect of the present application, the present application provides a method for preparing the above-mentioned potassium ion battery positive electrode material, the preparation method comprising:

[0011] According to the required raw material dosage in the molecular formula of the potassium ion battery positive electrode material, a mixture containing cobalt oxide, transition metal oxide, sodium salt and solvent is ball-milled, dried and sintered to obtain the potassium ion battery positive electrode material.

[0012] On the basis of the above technical solution, preferably, the cobalt oxide is tricobalt tetroxide.

[0013] On the basis of the above technical solution, preferably, the transition metal oxide includes manganese oxide and / or nickel oxide.

[0014] On the basis of the above technical solution, preferably, the manganese oxide is selected from at least one of manganese trioxide and manganese dioxide.

[0015] On the basis of the above technical solution, preferably, the nickel oxide is nickel oxide.

[0016] On the basis of the above technical solution, preferably, the sodium salt is selected from at least one of sodium carbonate and sodium acetate.

[0017] Based on the above technical solution, preferably, the solvent is selected from ethanol and / or acetone.

[0018] On the basis of the above technical solution, preferably, the molar volume ratio of the sodium salt to the solvent is 0.05-0.15:1 mmol / mL.

[0019] On the basis of the above technical solution, preferably, the rotation speed of the ball mill is 300-600 rpm, and the ball milling time is 8-12 h.

[0020] On the basis of the above technical solution, preferably, the rotation speed of the ball mill is independently selected from any value of 300rpm, 350rpm, 400rpm, 450rpm, 500rpm, 550rpm, 600rpm or a range between any two of the above.

[0021] On the basis of the above technical solution, preferably, the ball milling time is independently selected from any value among 8h, 8.5h, 9h, 9.5h, 10h, 10.5h, 11h, 11.5h, 12h or a range between any two of the above.

[0022] On the basis of the above technical solution, preferably, during the ball milling, the mass ratio of the raw material to the ball milling beads is 0.15 to 0.25.

[0023] On the basis of the above technical solution, preferably, during the ball milling, the diameter of the ball milling beads is 0.3 to 10 mm.

[0024] On the basis of the above technical solution, preferably, the drying temperature is 60-90° C., and the drying time is 8-16 hours.

[0025] On the basis of the above technical solution, preferably, the drying temperature is independently selected from any value of 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C or a range between any two of the above.

[0026] On the basis of the above technical solution, preferably, the drying time is independently selected from any value among 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h or a range between any two of the above.

[0027] On the basis of the above technical solution, preferably, the sintering temperature is 700-900° C., and the sintering time is 10-15 hours.

[0028] On the basis of the above technical solution, preferably, the temperature of the sintering treatment is independently selected from any value of 700°C, 750°C, 800°C, 850°C, 900°C or a range between any two of the above.

[0029] On the basis of the above technical solution, preferably, the sintering treatment time is independently selected from any value among 10h, 11h, 12h, 13h, 14h, 15h or a range between any two of the above.

[0030] As an optional implementation method, the present application is implemented through the following technical solutions:

[0031] The method for preparing the positive electrode material of a potassium ion battery of the present invention comprises:

[0032] (1) placing cobalt oxide, transition metal (manganese and / or nickel) oxide, sodium salt and solvent in a ball mill to obtain a viscous powder;

[0033] (2) drying the viscous powder to obtain a mixed metal powder;

[0034] (3) Sintering the material to obtain a positive electrode material.

[0035] In the potassium ion battery positive electrode material, the molar ratio of cobalt, transition metal (manganese and / or nickel) and sodium is (0.6-0.9): (0.1-0.4): (0.5-1).

[0036] The potassium ion battery positive electrode material of the present invention has the following beneficial effects compared with the prior art:

[0037] The potassium ion battery positive electrode material prepared by the present invention utilizes transition metal (manganese and / or nickel) elements to dope a layered cobalt-based oxide positive electrode material. After the transition metal (manganese and / or nickel) elements replace the cobalt sites, the manganese and / or nickel elements can break the original ordered structure of interlayer alkali metal ions and obtain a disordered structure of interlayer alkali metal ion vacancies. The structure can increase the diffusion path of potassium ions, inhibit multiple phase changes during charge and discharge of the potassium ion battery, reduce structural changes, thereby stabilizing the transition metal layer structure of the material, thereby further making the structure of the potassium ion battery positive electrode material more stable. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0039] Figure 1 X-ray diffraction patterns of the products provided in Example 1 and Comparative Example 1 of the present invention;

[0040] Figure 2 is a SEM image of the product provided in Comparative Example 1 of the present invention;

[0041] Figure 3 is a SEM image of the product provided in Example 1 of the present invention;

[0042] Figure 4 is a TEM image of the product provided in Example 1 of the present invention;

[0043] Figure 5 This is an X-ray photoelectron spectrum of the product provided in Comparative Example 1 of the present invention;

[0044] Figure 6 is the Co element X-ray photoelectron spectrum of the product provided in Example 1 of the present invention;

[0045] Figure 7 is an X-ray photoelectron spectrum of the Mn element of the product provided in Example 1 of the present invention;

[0046] Figure 8It is a cycle comparison diagram of the products provided by Examples 1-5 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0047] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0048] In the description of the embodiments of the present invention, unless otherwise clearly specified and limited, the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance; unless otherwise specified or explained, the term "multiple" refers to two or more; the terms "connected" and "fixed" should be understood in a broad sense, for example, "connected" can be a fixed connection, a detachable connection, an integral connection, or an electrical connection; it can be directly connected or indirectly connected through an intermediate medium. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0049] An embodiment of the present invention provides a method for preparing a positive electrode material for a potassium ion battery, comprising:

[0050] (1) placing cobalt oxide, transition metal (manganese and / or nickel) oxide, sodium salt and solvent in a ball mill to obtain a viscous powder;

[0051] (2) drying the viscous powder to obtain a mixed metal powder;

[0052] (3) Sintering the material to obtain a positive electrode material.

[0053] In this embodiment, a layered cobalt-based oxide positive electrode material is doped with transition metal (manganese or nickel) elements. After manganese replaces the cobalt active site, the multiple phase changes of the potassium ion battery positive electrode material during charging and discharging can be suppressed, and the structural changes can be reduced, thereby stabilizing the transition metal layer structure of the material.

[0054] In this embodiment, doping with manganese and / or nickel elements can break the original ordered structure of interlayer alkali metal ions and obtain a disordered structure of interlayer alkali metal ion vacancies, which can increase the diffusion path of potassium ions.

[0055] In some embodiments of the present invention, in the positive electrode material, the molar ratio of cobalt, transition metal (manganese and / or nickel) and sodium is (0.6-0.9): (0.1-0.4): (0.5-1).

[0056] In this embodiment, only when the molar ratio of cobalt, manganese and sodium in the raw material is (0.6-0.9): (0.1-0.4): (0.525-1.05) can the positive electrode material with a molar ratio of cobalt, manganese and sodium of (0.6-0.9): (0.1-0.4): (0.5-1) be obtained; only when the molar ratio of cobalt, nickel and sodium in the raw material is (0.6-0.9): (0.1-0.4): (0.525-1.05) can the positive electrode material with a molar ratio of cobalt, manganese and sodium of (0.6-0.9): (0.1-0.4): (0.525-1.05) be obtained. The molar ratio of cobalt, manganese, nickel and sodium is (0.6-0.9): (0.1-0.4): (0.5-1) for the positive electrode material; only when the molar ratio of cobalt, manganese, nickel and sodium in the raw materials is (0.6-0.9): (0.1-0.4): (0.1-0.4): (0.525-1.05) can the molar ratio of cobalt, manganese, nickel and sodium be (0.6-0.9): (0.1-0.4): (0.1-0.4): (0.5-1) for the positive electrode material be obtained;

[0057] When the molar ratio of the elements of the positive electrode material is within the above range, the structural stability of the positive electrode material is improved and the diffusion path of potassium ions is increased significantly.

[0058] In some embodiments of the present invention, the chemical formula of the positive electrode material includes Na 0.7 Co 0.75 Mn 0.25 O2、Na 0.7 Co 0.6 Mn 0.4 O2、Na 0.7 Co 0.75 Ni 0.25 O2、NaCo 0.75 Mn 0.25 O2、Na 0.5 Co 0.75 Mn 0.25 O2、Na 0.7 Co 0.8 Mn 0.1 Ni 0.1 O2.

[0059] In this embodiment, the chemical formula of the positive electrode material includes Na 0.7 Co 0.75 Mn 0.25 O2, the structural stability of the positive electrode material is improved and K + The diffusion rate increased most significantly.

[0060] In some embodiments of the present invention, the cobalt oxide includes cobalt trioxide, and the sodium salt includes sodium carbonate.

[0061] In this embodiment, the cobalt oxide includes cobalt tetroxide, the transition metal (manganese and / or nickel) oxide includes manganese trioxide or manganese dioxide or nickel oxide, and the sodium salt includes sodium carbonate or sodium acetate.

[0062] In some embodiments of the present invention, the solvent includes anhydrous ethanol.

[0063] In this embodiment, ethanol is selected as the solvent. Of course, other solvents, such as acetone, may also be selected as long as they can play a role of lubrication and cooling and are easily volatile.

[0064] In some embodiments of the present invention, in step (1), the ball milling time is 8-12 hours (for example, it can be 8 hours, 9 hours, 10 hours, 11 hours or 12 hours).

[0065] In this embodiment, ball milling can make various oxides mix evenly and at the same time, the particle size is smaller.

[0066] In some embodiments of the present invention, in step (1), the ball milling speed is 300-600 rpm (for example, 300 rpm, 400 rpm, 500 rpm or 600 rpm).

[0067] In this embodiment, the preferred rotation speed is 600 rpm.

[0068] In some embodiments of the present invention, in step (2), the drying time is 8-16 hours (for example, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours or 16 hours).

[0069] In this embodiment, drying can volatilize the solvent (such as anhydrous ethanol) in the material to obtain dry oxide powder.

[0070] In some embodiments of the present invention, in step (3), the sintering treatment temperature is 700-900° C., and the holding time is 10-15 hours.

[0071] In this embodiment, the preferred processing temperature is 801-900°C (for example, 810°C, 820°C, 830°C, 840°C, 850°C, 860°C, 870°C, 880°C, 890°C, 900°C).

[0072] In this embodiment, sodium carbonate or sodium acetate can be decomposed at high temperature to combine sodium ions with oxides to form positive electrode materials, and the decomposed anions form water and carbon dioxide and are discharged.

[0073] In order to more clearly illustrate the technical solutions and advantages of the present invention, the positive electrode material is described in detail below through examples.

[0074] Example 1

[0075] (1) 2.5 mmol of cobalt tetraoxide, 1.25 mmol of manganese trioxide, 3.675 mmol of sodium carbonate and 30 ml of anhydrous ethanol were placed in a ball mill and ball milled at a speed of 600 rpm for 12 h. The diameter of the ball milling beads during ball milling was 0.3-10 mm, and the mass ratio of the raw materials to the ball milling beads was 0.2. After ball milling, a mixed viscous powder was obtained;

[0076] (2) drying the obtained viscous powder in a forced air drying oven for 12 h at a temperature set at 70° C. to obtain a dry mixed powder;

[0077] (3) The material obtained in step (2) was placed in a tubular furnace and calcined at 850°C for 12 h with a heating rate of 5°C min -1 , thus obtaining the oxide Na 0.7 Co 0.75 Mn 0.25 O2.

[0078] Comparative Example 1

[0079] Comparative Example 1 is substantially the same as Example 1, except that in step (1), no manganese trioxide is added, and the positive electrode material obtained is Na 0.7 CoO2.

[0080] Example 2

[0081] (1) 2 mmol of cobalt tetraoxide, 2 mmol of manganese trioxide, 3.675 mmol of sodium carbonate and 30 ml of anhydrous ethanol were placed in a ball mill and ball milled at a speed of 300 rpm for 8 h. The diameter of the ball milling beads during ball milling was 0.3-10 mm, and the mass ratio of the raw materials to the ball milling beads was 0.25. After ball milling, a mixed viscous powder was obtained;

[0082] (2) drying the obtained viscous powder in a forced air drying oven for 16 h at a temperature set at 60° C. to obtain a dry mixed powder;

[0083] (3) The material obtained in step (2) was placed in a tubular furnace and calcined at 700°C for 15 h with a heating rate of 5°C min -1 The obtained positive electrode material is Na 0.7 Co 0.6 Mn 0.4 O2.

[0084] Example 3

[0085] (1) 2.5 mmol of cobalt tetraoxide, 2.5 mmol of nickel oxide, 3.675 mmol of sodium carbonate and 30 ml of anhydrous ethanol were placed in a ball mill and ball milled at a speed of 600 rpm for 12 h. The diameter of the ball milling beads during ball milling was 0.3-10 mm, and the mass ratio of the raw materials to the ball milling beads was 0.15. After ball milling, a mixed viscous powder was obtained;

[0086] (2) drying the obtained viscous powder in a forced air drying oven for 8 h at a temperature set at 90° C. to obtain a dry mixed powder;

[0087] (3) The material obtained in step (2) was placed in a tubular furnace and calcined at 900°C for 10 h with a heating rate of 5°C min -1 The obtained positive electrode material is Na 0.7 Co 0.75 Ni 0.25 O2.

[0088] Example 4

[0089] Example 4 is basically the same as Example 1, except that in step (1), 5.05 mmol of sodium carbonate is added, and the positive electrode material obtained is NaCo 0.75 Mn 0.25 O2.

[0090] Example 5

[0091] Example 5 is basically the same as Example 1, except that in step (1), 2.625 mmol of sodium carbonate is added, and the positive electrode material obtained is Na 0.5 Co 0.75 Mn 0.25 O2.

[0092] Example 6

[0093] Example 6 is basically the same as Example 1, except that in step (1), 2.67 mmol of cobalt tetraoxide, 0.5 mmol of manganese trioxide, and 0.5 mmol of nickel oxide are added, and the positive electrode material obtained is Na 0.7 Co 0.8 Mn 0.1 Ni 0.1 O2.

[0094] The embodiments and comparative examples were observed and tested to obtain Figures 1 to 8 .according to Figure 1 It can be seen that Na without manganese doping 0.7 CoO2 has a P2 structure, and after doping with manganese, Na 0.7 Co 0.75 Mn 0.25 The O2 material transforms into a P2 / P3 dual-phase structure. Figure 2 , Figure 3 The Na 0.7 CoO2 and Na in Example 1 0.7 Co 0.75 Mn 0.25 SEM images of O2 show that both materials are in the form of stacked sheets, while Na 0.7 The lamellar shape of CoO2 is more obvious. Figure 4 The Na in Example 1 is shown 0.7 Co 0.75 Mn 0.25 In the TEM image of O2, the interlayer spacing between two adjacent layers was measured to be 0.553 nm, which corresponds to the characteristic peak of the (002) crystal plane in the XRD card. Figure 5 The Na in Comparative Example 1 is shown 0.7 XPS diagram of CoO2 shows that the valence state of Co in the material is a mixed state of +2 and +3. Figure 6 , 7 The Na in Example 1 is shown 0.7 Co 0.75 Mn 0.25 From the XPS graph of O2, the proportion of +3-valent Co increases after doping, the average valence of Co increases, and the valence of Mn is +3 and +4. Figure 8 The electrochemical performance of the embodiments and various comparative examples is shown. 0.7 Co 0.75 Mn 0.25 O2 has the highest capacity due to its 0.7 CoO2, manganese doping expands the material's interlayer spacing and increases ion diffusion channels. When too much manganese is doped, due to Mn 3+ The Jahn-Teller effect, Na in Example 2 0.7 Co 0.6 Mn 0.4 The electrochemical cycle diagram of O2 fluctuates greatly and is not stable enough. After nickel doping, the material is relatively stable, but the capacity is low. This situation is improved after manganese and nickel co-doping. The capacity is increased while the retention rate is relatively stable, proving that nickel contributes less to the capacity. The improvement in stability after nickel or manganese and nickel doping comes from the more stable structure of the material after entropy increase. When the sodium ion content changes, NaCo 0.75 Mn 0.25 O2 and Na 0.5 Co 0.75 Mn 0.25 O2 retention rate is similar, but the capacity is higher than Na 0.7 Co 0.75 Mn 0.25 O2 is slightly lower.

[0095] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A positive electrode material for a potassium ion battery, characterized in that: The molecular formula of the positive electrode material of the potassium ion battery is Na x Co y A z O2, x, y, z are all atomic numbers, A is a transition metal element; Among them, 0.5≤x≤1, 0.6≤y≤0.9, 0.1≤z≤0.4; The transition metal element is selected from Mn and / or Ni.

2. The potassium ion battery positive electrode material according to claim 1, characterized in that The molecular formula of the positive electrode material of the potassium ion battery includes Na 0.7 Co 0.75 Mn 0.25 O2、Na 0.7 Co 0.6 Mn 0.4 O2、Na 0.7 Co 0.75 Ni 0.25 O2、NaCo 0.75 Mn 0.25 O2、Na 0.5 Co 0.75 Mn 0.25 O2、Na 0.7 Co 0.8 Mn 0.1 Ni 0.1 One of O2.

3. The method for preparing a positive electrode material for a potassium ion battery according to claim 1 or 2, characterized in that: The preparation method comprises: According to the required raw material dosage in the molecular formula of the potassium ion battery positive electrode material, a mixture containing cobalt oxide, transition metal oxide, sodium salt and solvent is ball-milled, dried and sintered to obtain the potassium ion battery positive electrode material.

4. The preparation method according to claim 3, characterized in that: The cobalt oxide is tricobalt tetroxide.

5. The preparation method according to claim 3, characterized in that: The transition metal oxide includes manganese oxide and / or nickel oxide.

6. The preparation method according to claim 5, characterized in that: The manganese oxide is selected from at least one of manganese trioxide and manganese dioxide; The nickel oxide is nickel oxide.

7. The preparation method according to claim 3, characterized in that: The sodium salt is selected from at least one of sodium carbonate and sodium acetate; The solvent is selected from ethanol and / or acetone; The molar volume ratio of the sodium salt to the solvent is 0.05-0.15:1 mmol / mL.

8. The preparation method according to claim 3, characterized in that: The ball milling speed is 300-600 rpm, and the ball milling time is 8-12 hours; During the ball milling, the mass ratio of the raw material to the ball milling beads is 0.15 to 0.25; During the ball milling, the diameter of the ball milling beads is 0.3-10 mm.

9. The preparation method according to claim 3, characterized in that: The drying temperature is 60-90° C., and the drying time is 8-16 hours.

10. The preparation method according to claim 3, characterized in that: The sintering temperature is 700-900° C., and the sintering time is 10-15 hours.

Citation Information

Patent Citations

  • Layered metal oxide Na0. 7MnO2.05 and preparation method thereof

    CN117902631A

  • P2 / P3 biphase symbiotic K0. 7Mn0. 67Ni0. 33O2 layered oxide material as well as preparation method and application thereof

    CN118367099A

  • Storage device and storage method

    KR1020210145679A